Rational Use of Leads in Artificial Cardiac Pacing - Duarte, Carlos Eduardo; Sbaraini, André Brambilla (JOURNAL OF CARDIAC ARRHYTHMIAS, 2020)
Introduction: Cardiovascular implantable electronic device (CIEDs) are a proven therapy for the treatment of bradyarrhythmias, prevention of sudden death or heart failure. Since the first transvenous pacemaker implantation more than 60 years ago, technological advances in devices and improvements in surgical techniques have occurred. However, this type of therapy is still associated with significant complications, most of them related to the implantation of transvenous leads. Objective: To present a reflection on how to practice the rational use of lead implantation and propose strategies and alternatives to delay or avoid it, based on the current knowledge in the various fields of artificial cardiac stimulation. Methods: Review of literature that used articles from 1995 to 2019, from several platforms and periodicals. Conclusion: There is an expectation that in the coming years there will be technological and knowledge advances in the field of leadless stimulation, allowing these devices to be incorporated into clinical practice in a routine manner. Currently, if the implantation of ventricular electrodes in cases of sinus node disease with preserved atrioventricular conduction is rationalized, the implantation of atrial electrodes in implantable cardioverter-defibrillators (ICD) without the necessity of antibradicardia stimulation or ventricular electrodes in cases without the necessity of antitachycardia stimulation (ATP) considering the subcutaneous ICD implantation, this article will have fulfilled its role.